Blood pressure and heart rate in patients with ischaemic heart disease receiving nifedipine and propranolol. Issue 6323 (17th April 1982) - Harris, L; Dargie, H J; Lynch, P G; Bulpitt, C J; Krikler, D M
Abstract : A randomised controlled crossover trial was performed to assess the anti-anginal effects of nifedipine and propranolol separately and together. The effects of these treatments on blood pressure and heart rate were assessed at rest and after the cold pressor and mental arithmetic tests. Nifedipine and propranolol together produced the greatest reduction in supine and erect systolic and diastolic blood pressures. Propranolol (480 mg daily) lowered resting systolic/diastolic blood pressures by 7/6 mm Hg and nifedipine (60 mg daily) lowered it by 10/8 mm Hg, while in the erect position the hypotensive effect of these agents averaged 9/8 mm Hg. During the cold pressor test propranolol lowered the maximum pressure by an average of 11/6 mm Hg and nifedipine by 19/10 mm Hg. For the mental arithmetic test, the results were 7/2 mm Hg and 16/7 mm Hg respectively. Propranolol (480 mg daily)reduced supine and erect heart rate by 19 and 25 beats/minute respectively, while nifedipine did not alter heart rate significantly. The favourable haemodynamic responses to nifedipine suggest that it may be of value in the management of hypertension.